Influential parameters of surface waters on the formation of coating on TiO2 nanoparticles under natural conditions. Issue 11 (28th September 2021) - Tayyebi Sabet Khomami, Narjes; Patel, Parthvi Mayurbhai; Jusi, Cynthia Precious; Trouillet, Vanessa; David, Jan; Schaumann, Gabriele E.; Philippe, Allan
Abstract : Investigation of the natural coatings on nanoparticles in surface waters (using dialysis bags), and evaluation of the influential parameters of surface waters on the formation of these coatings. Abstract : Formation of natural coatings on nanoparticles in aquatic media is highly influenced by the dynamic composition of the medium. Hundreds of research articles were dedicated to this question and an in-depth understanding of the underlying mechanisms has been obtained for some materials. Nonetheless, it is still unknown to which extent these results obtained under controlled conditions in the laboratory can be extrapolated to environmental conditions. In this study, we used the recently introduced dialysis bag method to expose n-TiO2 in situ to 18 surface waters with contrasting physicochemical parameters by varying the sampling location and season and characterized the resulting natural coatings. ATR-FTIR and 2D-IR spectroscopy (thermal perturbation), thermogravimetry, and X-ray photoelectron spectroscopy analyses of the exposed nanoparticles revealed clear differences in the composition of the natural coatings in the presence of both organic (carboxylate and aromatic groups) and inorganic (carbonate) components. Subsequently, multivariate data analysis (correlation matrix, principal component analysis, and random forest) was used to explore the relationships between surface water parameters and the composition of the natural coating; the results enabled us to identify pH, electrical conductivity, and Ca 2+ –Mg 2+ concentration as the three most important parameters for predicting the composition of the natural coating of TiO2 nanoparticles.